Isolamento, avaliação e caracterização de Bacillus thuringiensis, com potencial para controle de diptera e lepidoptera - Gobatto, Vaneisa (My University, 2014)
Among the insects that harm the socioeconomic development of Serra Gaúcha, exist the dipterous, of the family Simuliidae that, due to its hematofagic process, cause discomfort and allergies to active rural tourists. In the agricultural regions, the lepidopterous, of the family Noctuidae, constitute curses of several cultures, constituting an economical prejudice. Seeking to reduce the use of chemical substances in the control of insects, this work is aimed at isolating the bacteria Bacillus thuringiensis (Bt) for the application of regional programs of Simulids and Noctuids pest control. Samples of insects and of soil of rural and urban areas were collected in the municipal districts of the specific area. Were obtained 721 bacterial colonies, from which, 231 (32,03%) were identified as Bt. Patogenicity tests against Culex quinquefasciatus and Anticarsia gemmatalis were executed with 84 bacteria isolated from soil and 28 bacteria isolated from insects that had a larger capacity of cellular reproduction. The results indicated that the isolated bacteria recovered from the insects were more specific, considering that a larger number of bacteria coming from the soil were more toxic for both species, showing a wider spectrum of entomopatogenic. Just one of the isolated 12 bacteria presented a similar value of CL50 than the one obtained with the lineage pattern IPS-82, in relation of the mortality rate of larvae of C. quinquefasciatus. The profile of the protoxins of one of the isolated ones is characterized by SDS-PAGE, demonstrating that two isolated bacteria obtained from the dipteran, had a similar profile as lineage IPS-82, while two others isolated from the soil, with bands between 65 and 130 kDa, were more toxics for lepidopteran and the two obtained from the soil and three obtained from of insects, and presented one band of approximately 120 kDa, being more effective against caterpillars.
Entre os insetos que prejudicam o desenvolvimento sócio-econômico na Serra Gaúcha, encontram-se os dípteros da família Simuliidae, que devido a hematofagia, provocam desconforto e alergias, interferindo no turismo rural. Na área agrícola, os lepidópteros da família Noctuidae, são pragas de diversas culturas, sendo economicamente relevantes. Visando reduzir o uso de substâncias químicas que normalmente são empregadas no controle destes insetos, este trabalho objetivou obter isolados de Bacillus thuringiensis (Bt) para a aplicação em programas regionais de controle de simulídeos e noctuídeos. Utilizando-se amostras de solo da área rural e urbana e de insetos, coletados em municípios da Região, obtiveram-se 721 colônias bacterianas, das quais, 231 (32,03%) foram identificadas como Bt. Testes de patogenicidade contra Culex quinquefasciatus e Anticarsia gemmatalis com 84 isolados de solo e 28 de insetos selecionados por apresentarem elevada taxa de esporulação, indicaram que os recuperados de insetos foram mais específicos, enquanto que maior número dos provenientes de solo foram tóxicos para ambas as espécies, indicando mais amplo espectro entomopatogênico. Apenas um dos 12 isolados apresentou valor de CL50 similar àquele obtido com a linhagem padrão IPS-82, em relação a mortalidade de larvas de C. quinquefasciatus. O perfil das protoxinas dos isolados foi caracterizado por SDS-PAGE, demonstrando que dois isolados obtidos de díptero, tiveram um perfil semelhante a linhagem IPS-82, enquanto dois isolados de solo, com bandas entre 65 e 130 kDa, foram mais tóxicos para lepidópteros e dois obtidos de solo e três de insetos, apresentaram uma banda de aproximadamente 120 kDa, sendo mais efetivos contra lagartas.
Keywords: Entomologia agricola; Biotecnologia; Microbiologia; Bacillus thuringiensis; Insetos; Controle biológico; Diptera; Lepidoptera; Biotechnology; Microbiology; Insects; Biological control